1973 թ. արաբա–իսրայելյան պատերազմը և Հորդանանի դիրքորոշումը - Վիրաբյան, Դավիթ («Զանգակ - 97»)
In 1973 Jordan wasn't involved in the Arab-Israeli war as Syria and Egypt. There were some reasons for this. The presence of the Palestinians with their military organi&ations which created in Jordan a "state in the State", negative attitudc of the Jordanien society and the role of the USA. In addition to the above mentioned thcre was the negative position of neighbouring Arab countries towards the Kingdom of Jordan, which at that time was facing economic problems.
Keywords: Պատմություն; Քաղաքականություն